Innovative Technology and Pedagogical Approaches Adoptions in Achieving Sustainable Development: Perspective of Science Educators in Nigeria - Ibrahim Abdulmuhsin; Ahmed Abiola Tawa (Fakultas Pertanian, 2026)
This study investigated how science educators in Nigerian universities use cutting-edge tools and instructional techniques to promote sustainable development. In Ilorin, Kwara State, 45 science educators from public and private universities participated in a descriptive survey using a 25-item structured questionnaire. The study evaluates the degree of new technology adoption, the kinds of pedagogical strategies used, and the difficulties teachers encounter while using these tactics. The findings suggest that although there is still little institutional support for these projects, there is a moderate level of adoption of technology such as interactive whiteboards and mobile learning apps. Although pedagogical approaches like inquiry-based and project-based learning are frequently used, more uniformity among teachers could still be achieved. The main issues noted are faculty and student resistance to change, a lack of professional development opportunities, and inadequate access to resources. In order to successfully integrate cutting-edge technologies and instructional strategies for sustainability education, the study emphasizes the significance of bolstering institutional support, offering more thorough training programs, and resolving resistance.